Dynamic jaws and dynamic couch in helical tomotherapy - Sterzing, Florian; Uhl, Matthias; Hauswald, Henrik; Schubert, Kai; Sroka-Pérez, Gabriele; Chen, Yu; Lu, Weiguo; Mackie, Rock; Debus, Jürgen; Herfarth, Klaus; Oliveira, Gustavo (International journal of radiation oncology, biology, physics, 2010)
Purpose - To investigate the next generation of helical tomotherapy delivery with dynamic jaw and dynamic couch movements. - Methods and Materials - The new technique of dynamic jaw and dynamic couch movements is described, and a comparative planning study is performed. Ten nasopharyngeal cancer patients with skull base infiltration were chosen for this comparison of longitudinal dose profiles using regular tomotherapy delivery, running-start-stop treatment, and dynamic jaw and dynamic couch delivery. A multifocal simultaneous integrated boost concept was used (70.4Gy to the primary tumor and involved lymph nodes; 57.4Gy to the bilateral cervical lymphatic drainage pathways, 32 fractions). Target coverage, conformity, homogeneity, sparing of organs at risk, integral dose, and radiation delivery time were evaluated. - Results - Mean parotid dose for all different deliveries was between 24.8 and 26.1Gy, without significant differences. The mean integral dose was lowered by 6.3% by using the dynamic technique, in comparison with a 2.5-cm-field width for regular delivery and 16.7% with 5-cm-field width for regular delivery. Dynamic jaw and couch movements reduced the calculated radiation time by 66% of the time required with regular 2.5-cm-field width delivery (199 sec vs. 595 sec, p < 0.001). - Conclusions - The current delivery mode of helical tomotherapy produces dose distributions with conformal avoidance of parotid glands, brain stem, and spinal cord. The new technology with dynamic jaw and couch movements improves the plan quality by reducing the dose penumbra and thereby reducing the integral dose. In addition, radiation time is reduced by 66% of the regular delivery time.